2019
DOI: 10.21977/d914140829
|View full text |Cite
|
Sign up to set email alerts
|

Integrating the Arts into Science Teaching and Learning: a Literature Review

Abstract: Science is creative. Write it big, shout it loud, because the message is not getting through. (Howe, 2004, p.14) The American educational system has experienced a recent and increased focus on Science, Technology, Engineering, and Mathematics (STEM), and researchers and practitioners have argued for equal emphasis on the arts as well. According to Hartle and colleagues, incorporating the arts into learning is considered important and useful for four basic reasons (Hartle, Pinciotti, & Gorton, 2015). First, all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…Arts integration develops arts-based methods, which we understand as activating and pedagogical forces promoting indeterminacy and openness for spaces of transformation. A comprehensive international review of arts and science integration within schools (Green et al, 2018) found that arts integration improved science academic performance as well as general use and understanding of science vocabulary. Ralph Buck and Barbara Snook (2016) found improved understanding of science concepts within their New Zealand based arts and science combined study.…”
Section: Arts Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…Arts integration develops arts-based methods, which we understand as activating and pedagogical forces promoting indeterminacy and openness for spaces of transformation. A comprehensive international review of arts and science integration within schools (Green et al, 2018) found that arts integration improved science academic performance as well as general use and understanding of science vocabulary. Ralph Buck and Barbara Snook (2016) found improved understanding of science concepts within their New Zealand based arts and science combined study.…”
Section: Arts Integrationmentioning
confidence: 99%
“…Ralph Buck and Barbara Snook (2016) found improved understanding of science concepts within their New Zealand based arts and science combined study. Previous research combining arts and science in creative practices further demonstrates a significant opportunity to develop the emotional and behavioral foci in educational programs and projects (Buck & Snook, 2016;Green et al, 2018;Ward, 2005;Winks et al, 2020;Østern & Strømme, 2014;Østern et al, 2019). The arts can play an inclusive, dynamic, and leading role in engaging children and young people's visions for the valuing of water in sustainable ways that are relevant to those children's and young people's cultural and geographical contexts.…”
Section: Arts Integrationmentioning
confidence: 99%
“…Astronomical images using telescopes provides vital scientific information for the development of space exploration and furthering knowledge. Research into the influence of incorporating art and imagery [71,72] to improve girls' science engagement demonstrates the importance for the use of astronomical imaging technologies to increase the future success of women in astronomy. A potential significant outcome in the study of the impact of telescope use is improving access for women and minorities to the STEM pipeline [15,21,22,[73][74][75][76][77].…”
Section: B Science Identitymentioning
confidence: 99%
“…Integrated learning activities aim to create more enticing learning activities as well as rich in content. For example, the integration between science and art, where children taught not only the ability to think scientifically but also the aesthetics of art simultaneously [23]. González study stated that involving children in science activities presents challenges for children [24].…”
Section: Early Childhood Science Learning Programmentioning
confidence: 99%